PENGARUH TAKE OVER, GROWTH OPTION, DAN BONUS ISSUE TERHADAP KEBIJAKAN REVALUASI ASSET TETAP (Studi Empiris Pada Seluruh Perusahaan yang Terdaftar di BEI Tahun 2017 -2020) - Kamila Kamila; Anik Malikah; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to analyze the effect of take over, growth option, and bonus issue on fixed asset revaluation policy. The research population is all companies listed on the IDX during 2017-2020. The number of samples is 60 companies for 4 years. The data analysis technique used is logistic regression. The results of this study indicate that take over, growth option has a significant effect on fixed asset revaluation policy, bonus issue has no significant effect on fixed asset revaluation policy. Simultaneously, all take over growth option and bonus issue variables have a significant effect on fixed asset revaluation policies.Keywords: take over, growth option, and bonus issue